Evidence for glucocorticoid‐mediated hypertension after uninephrectomy. Issue 5 (11th October 2013) - Huesler, Carina; Lauterburg, Meret; Frey, Brigitte M.; Frey, Felix J.
Abstract: Recently, evidence was presented that uninephrectomy induces salt‐sensitive hypertension in rats. The increase in blood pressure was abrogated by a mineralocorticoid receptor antagonist but not by an aldosterone synthase inhibitor. Here, we hypothesize that mineralocorticoid receptor activation occurred by an 11beta‐hydroxy‐glucocorticosteroid, as a consequence of dysregulated 11beta‐hydroxysteroid dehydrogenase enzymes. Therefore, 3‐week‐old Sprague‐Dawley rats were either uninephrectomized or sham operated and given a normal (0.4%) or high (8%)‐salt diet. At week 8, a telemetric device was implanted, and during week 13 blood pressure continuously measured and urine was collected. The animals were sacrificed thereafter and liver and kidney were harvested. Steroid metabolites were analyzed by GC‐MS and mRNA assessed by PCR. Uninephrectomy caused a distinct salt‐sensitive hypertension. The increase in blood pressure correlated significantly with a decline in the apparent activity of 11beta‐hydroxysteroid dehydrogenase 2 and an increase of 11beta‐hydroxysteroid dehydrogenase 1, when urinary corticosterone metabolites were considered. These results were mirrored by the corresponding metabolite ratios assessed in renal and liver tissue. Changes in enzyme activities were in part explained by changes in the mRNA content. In conclusion, mineralocorticoid receptor‐dependent salt sensitivity after UNX in rats appears to be mediated by glucocorticoids. Abstract : e00101 Abstract : Funder et al and Edwards et al proposed that a pre‐receptor mechanism allows to inactivate corticosterone and cortisol in mineralocorticoid target tissues (Fig. 1). Thus, we hypothesized that a dysregulation of this pre‐receptor mechanism, the 11β‐hydroxysteroid dehydrogenase enzymes (11βHSD), causes a glucocorticoid‐mediated MR‐activation after UNX in rats on a high salt diet. Our observations indicate an enhanced availability of glucocorticoids due to an increased 11βHSD1 and a diminished 11βHSD2.